Implementation of Filing System at SMPN 23 Palembang - Afif Alfiyanto; Muhammad Ghazali; Fitri Hidayati; Wulan Sari; Ivan Riyadi (Sustainable Jurnal Kajian Mutu Pendidikan, 2023)
The research set out to determine the status of the filing system at SMPN 23 Palembang, as well as the variables that helped and hindered its introduction. The study employs a descriptive qualitative approach, with the superintendent providing the study's key piece of information and principals and teachers providing additional context. Methods of gathering information such as conducting interviews and keeping detailed records. Methods for analyzing data include summarization, validation, and drawing conclusions. The findings of this research demonstrate that SMPN 23 Palembang's file system implementation is pretty excellent in numerous respects. This is especially true in terms of Direction, which is carried out to ensure that the filing system implementation proceeds in accordance with all relevant rules and regulations. The principal provides encouragement to the office staff and instructors to get them excited about using the new file system. There is a strong correlation between the effectiveness of the file system in disseminating information and the quality of communication between the principal, administrative personnel, and teachers. Coordination, in the sense of making sure that the principals, administrators, and teachers all work together to roll out the new file system. Use of a suitable archive storage system and efficient archival communication are two of the pillars upon which the archiving system rests. The lack of skilled workers and inadequate physical space for archives are major impediments.